Soft drink consumption among Saudi women: patterns and influencing factors - Almoayad, Fatmah; Alzaben, Abeer Salman; Mortada, Eman M.; Alshaalan, Rasha; Benajiba, Nada; Bawazeer, Nahla; Alabdulkader, Shahd (Frontiers in Public Health, 2025)
ObjectiveSaudi Arabia has one of the highest prevalences of obesity worldwide, and excessive consumption of sweetened soft drinks significantly contributes to this. In this study, we investigated the patterns of soft drink consumption among Saudi women and identified the socio-demographic and attitudinal factors influencing these patterns.DesignWe studied 1,555 Saudi women aged 20–60 years between October 2022 and March 2023. An online questionnaire was used to collect information regarding demographics, consumption patterns, attitudes towards soft drinks, and the factors influencing consumption. Chi-square tests and regression analyses were used to identify significant associations and statistical predictors of consumption frequency.ResultsThe respondents were categorized into infrequent soft drinks consumers (58.9%) and frequent consumers (41.1%). Significant associations of soft drink consumption patterns with age, marital status, educational level, income, and other factors were identified. Relative youth, low educational level, and low income were negatively associated with soft drink consumption, whereas a positive attitude towards soft drinks emerged as a significant predictor of higher frequency of consumption.ConclusionThe results of this study demonstrate the high prevalence of soft drink consumption by Saudi women and the complex interplay of socio-demographic factors and attitudes with consumption patterns. Public health strategies aimed at mitigating the health risks associated with excessive soft drink consumption should focus on education and awareness campaigns tailored to various demographic groups. Although predictors were identified, causal conclusions cannot be drawn due to the cross-sectional nature of the study.